Dietary protein intake and incidence of type 2 diabetes in Europe: the EPIC-InterAct Case-Cohort Study. - van Nielen, M; Feskens, E; Mensink, M; Sluijs, I; Molina, E; Amiano, P; Ardanaz, E; Balkau, B; Beulens, J; Boeing, H; Clavel-Chapelon, F; Fagherazzi, G; et al. (American Diabetes Association Inc., 2014)
OBJECTIVE: The long-term association between dietary protein and type 2 diabetes incidence is uncertain. We aimed to investigate the association between total, animal, and plant protein intake and the incidence of type 2 diabetes. RESEARCH DESIGN AND METHODS: The prospective European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct case-cohort study consists of 12,403 incident type 2 diabetes cases and a stratified subcohort of 16,154 individuals from eight European countries, with an average follow-up time of 12.0 years. Pooled country-specific hazard ratios (HRs) and 95% CI of prentice-weighted Cox regression analyses were used to estimate type 2 diabetes incidence according to protein intake. RESULTS: After adjustment for important diabetes risk factors and dietary factors, the incidence of type 2 diabetes was higher in those with high intake of total protein (per 10 g: HR 1.06 [95% CI 1.02-1.09], P(trend) < 0.001) and animal protein (per 10 g: 1.05 [1.02-1.08], P(trend) = 0.001). Effect modification by sex (P < 0.001) and BMI among women (P < 0.001) was observed. Compared with the overall analyses, associations were stronger in women, more specifically obese women with a BMI >30 kg/m(2) (per 10 g animal protein: 1.19 [1.09-1.32]), and nonsignificant in men. Plant protein intake was not associated with type 2 diabetes (per 10 g: 1.04 [0.93-1.16], P(trend) = 0.098). CONCLUSIONS: High total and animal protein intake was associated with a modest elevated risk of type 2 diabetes in a large cohort of European adults. In view of the rapidly increasing prevalence of type 2 diabetes, limiting iso-energetic diets high in dietary proteins, particularly from animal sources, should be considered.